Point and figure charting : the essential application for forecasting and tracking market prices - Dorsey, Thomas J. (Wiley trading., 2013)
An up-to-date look at point and figure charting from one of the foremost authorities in the field If you're looking for an investment approach that has stood the test of time-during both bull and bear markets-and is easy enough to learn, whether you're an expert or aspiring investor, then Point and Figure Charting, Fourth Edition is the book for you. Filled with in-depth insights and expert advice, this practical guide will help you grow your assets in any market. In this reliable resource, the world's top point and figure charting expert, Tom Dorsey returns to explain how tr.